Effects of lipoxygenase metabolites of arachidonic acid on the growth of human mononuclear marrow cells and marrow stromal cell cultures - V. Desplat; F. Dupuis; F. Trimoreau; C. Dulery; V. Praloran; Y. Denizot (Mediators of Inflammation)
The effects of various lipoxygenase metabolites of arachidonic acid (AA) were investigated on the growth of freshly isolated human bone marrow mononuclear cells and marrow stromal cell cultures. LTB4, LXA4, LXB4, 12-HETE and 15-HETE (1 μM) decreased [3H]-thymidine incorporation on marrow stromal cell cultures without affecting cell number. Only 12-HETE showed a dose-response effect on [3H]-thymidine incorporation. While LTB4 (1 μM) decreased thymidine incorporation on marrow mononuclear cells, LTC4, LXA4, LXB4, 12-HETE and 15-HETE had no effect. The lipoxygenase inhibitor NDGA had no effect on both cell types suggesting no role of endogenous lipoxygenase metabolites on cell growth. These results suggest no important role of lipoxygenase metabolites of AA on the proliferation of human marrow mononuclear cells and marrow stromal cell cultures.